Improving Elementary Students’ Mathematics Learning Outcomes on Fraction Operations through the Course Review Horay Learning Model - Dona, Yuliandra (Journal of Teaching and Education, 2025)
This study aimed to improve students’ mathematics learning outcomes on fraction operations through the implementation of the Course Review Horay (CRH) learning model. The research was conducted as Classroom Action Research (CAR) involving students of an elementary school class. The study was carried out in two cycles, each consisting of planning, action, observation, and reflection stages. Data were collected through learning outcome tests, observation sheets, and documentation. Quantitative data were analyzed by calculating the percentage of students’ learning mastery, while qualitative data were analyzed descriptively to describe students’ learning activities and classroom conditions. The results showed a significant improvement in students’ learning outcomes after the implementation of the CRH learning model. In the first cycle, students’ learning mastery had not yet met the predetermined criteria, indicating the need for instructional improvement. After revising the teaching strategy in the second cycle, students’ participation increased, learning activities became more interactive, and the percentage of students achieving mastery learning improved significantly. These findings indicate that the Course Review Horay learning model effectively enhances students’ understanding of fraction operations and creates an enjoyable learning atmosphere. Based on the results, it can be concluded that the Course Review Horay model is effective in improving mathematics learning outcomes and students’ engagement in elementary school mathematics learning. Therefore, this model is recommended as an alternative instructional strategy to support active and meaningful learning.